THE PROFILE AND ASSOCIATED RISK FACTORS OF DIABETIC FOOT DISEASE AMONG PATIENTS WITH TYPE 2 DIABETES MELLITUS SEEN AT PRIVATE SPECIALTY CLINICS AT ST. LUKE’S MEDICAL CENTER - Lim, Krizia Marie; Lopez, Denise Joy; Bautista, Carmela Veronica; Dampil, Oliver Allan (Journal of the ASEAN Federation of Endocrine Societies, 2023)
INTRODUCTION Diabetic foot disease is a debilitating complication of diabetes mellitus and is a major source of morbidity, mortality, and reduced quality of life. Determining the risk factors for diabetic foot ulcers is important to prevent the devastating consequences among patients with diabetes. This study aims to determine the profile and associated risk factors of diabetic foot disease among patients diagnosed with type 2 diabetes mellitus being seen in private specialty clinics. METHODOLOGY A single-center, analytical cross-sectional study was conducted at St. Luke’s Medical Center, Quezon City among patients with type 2 diabetes mellitus. Clinical information and laboratory results were obtained during the time of consultation, and patients were classified as either low risk, moderate risk, high risk for diabetic foot disease, or active foot disease. The interaction between various risk factors was explored by multivariate analysis. RESULTS A total of 129 adult patients with diabetes mellitus were evaluated using the Diabetes Foot Screening and Risk Stratification Tool from January to May 2021. The demographic and clinical profile of the study showed that the proportion of patients with neuropathy (χ2 = 60.66, p = 0.001), long duration of diabetes (F = 5.92, p = 0.004), and low estimated glomerular filtration rate (eGFR) (F = 3.70, p = 0.023) was significantly higher in patients with moderate to high risk for diabetic foot disease. Univariate polynomial logistic regression analyses showed that neuropathy greatly increased the odds of having moderate (OR = 115.63, p = 0.001) and high-risk stratification (OR = 166.50, p = 0.001). Other factors were also noted to affect the risk stratification for diabetic foot disease such as duration of diabetes (OR = 1.09, p = 0.004) and hypertension (OR = 2.45, p = 0.027). On the other hand, normal eGFR (OR = –1.02, p = 0.011), left normal ankle brachial pressure index (OR = –4.32, p = 0.042), and good glycemic control (OR = –5.41, p = 0.050) significantly decrease the likelihood of having high-risk stratification for diabetic patients. CONCLUSION Those most susceptible to developing a high risk for diabetic foot disease were patients with neuropathy, hypertension, and a long duration of diabetes. High-risk patients with the given profile should be closely followed to prevent diabetesrelated complications.